Sarcoidosis: Pathogenesis, Diagnosis, and Clinical Management - Kuliga, Marcin; Mateusz Bajak; Dominik Maciej Feret; Jadwiga Inglot; Julia Inglot; Maciej Mamczur; Julia Słowik; Damian Sowa; Michał Szczepański; Daniel Zapasek (Quality in Sport, 2024)
Introduction: Sarcoidosis is a multisystem inflammatory disease of unknown etiology. It is more common in women and in people suffering from obesity. A characteristic feature is the formation of non-sarcomatous granulomas, which could occure important organs. It could also present as an asymptomatic form, and its diagnosis may be made incidentally on a routine chest X-ray. Aim of the study: The aim of this study was to review the literature describing the disease sarcoidosis-its course, clinical forms, diagnosis and treatment. Methods and materials: : We reviewed the literature available in the PubMed database, using the key words: "sarcoidosis"; "granulomatosis’’; “cardiac sarcoidosis”; “neurosarcoidosis”; "pulmonary sarcoidosis’’. Results: The most common form of sarcoidosis is pulmonary, with enlargement of hilar lymph nodes and parenchymal lesions. The disease could manifest itself in the form of skin lesions-specifically and non-specifically, ocular lesions, where nay most often appears as uveitis, usually bilateral, and could also involve the heart. Patients with neurosarcoidosis usually have involvement of the pituitary, hypothalamus, meninges and cranial nerves. Conclusion: The diagnosis of sarcoidosis is difficult because its symptoms are often nonspecific. Diagnosis is based on exclusion of other diseases and is confirmed through imaging, histopathological, and immunological tests. In most cases, the prognosis of sarcoidosis is positive, and the disease may resolve spontaneously or under treatment. Treatment of sarcoidosis depends on the severity of the disease and the involvement of specific organs, the most common treatment is glucocorticoids.